Spermiogenesis and spermatozoon of the tapeworm Parabothriocephalus gracilis (Bothriocephalidea): Ultrastructural and cytochemical studies - Sipkova, L.; Levron, C.; Freeman, M.; Scholz, T. (Versita, 2010)
Spermiogenesis and spermatozoon ultrastructure of the tapeworm Parabothriocephalus gracilis were described using transmission electron microscopy (TEM). Spermiogenesis is characterized by the formation of a zone of differentiation with two centrioles associated with striated rootlets, and an intercentriolar body between them. The two flagella undergo a rotation of 90 until they become parallel to the median cytoplasmic extension with which they fuse. Electron-dense material is present in the apical region of the zone of differentiation in the early stages of spermiogenesis. This electron-dense material is characteristic for the orders Bothriocephalidea and Diphyllobothriidea. The mature spermatozoon contains two axonemes of the 9 + `1' trepaxonematan pattern, nucleus, parallel cortical microtubules and electron-dense granules of glycogen. The anterior extremity of the spermatozoon exhibits a single helical electron-dense crested body 130 nm thick. One of the most interesting features is the presence of a ring of cortical microtubules surrounding the axoneme. This character has been reported only for species of the order Bothriocephalidea and may be unique in this cestode group.